J. Glob. Power Propuls. Soc. 2017
DOI: 10.22261/2ii890
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of turbulence model predictions for a centrifugal compressor simulation

Abstract: Steady-state computational fluid dynamics (CFD) simulations are an essential tool in the design process of centrifugal compressors. Whilst global parameters, such as pressure ratio and efficiency, can be predicted with reasonable accuracy, the accurate prediction of detailed compressor flow fields is a much more significant challenge. Much of the inaccuracy is associated with the incorrect selection of turbulence model. The need for a quick turnaround in simulations during the design optimisation process also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…Following [11][12][13][14] the k-SST model was selected. The chosen k-SST model is widely used and has been validated for turbomachinery applications [20].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following [11][12][13][14] the k-SST model was selected. The chosen k-SST model is widely used and has been validated for turbomachinery applications [20].…”
Section: Methodsmentioning
confidence: 99%
“…This is the same approach as used in [7,18]. The combination of a total pressure and temperature inlet with a mass flow rate outlet is the approach favoured for stability [11]. The hub and shroud for the inlet and diffuser domains, the hub for the impeller domain, and the blades themselves were set to wall (adiabatic, no slip, and smooth wall) boundary conditions.…”
Section: Boundary Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Near surge conditions, significant differences between turbulence models occur because the predicted fully separated flow in blade passages is highly depended on the modeled turbulent viscosity, but there seems to be no universal turbulence model that is always superior to others [31]. Assessment of turbulence models in centrifugal compressors were carried out in the SRV2-O case [32] and the Radiver case [33]. It is generally found that the Spalart-Allamaras model, the k-ω shear stress transport model, the v 2 -f-k-ε Durbin model and the Reynolds stress model can predict very similar flow features at the impeller peak efficiency condition, but the Spalart-Allamaras model has limitations in vaned diffuser flow fields where the fully separated flow is dominate.…”
Section: Methodsmentioning
confidence: 99%